MATERNAL AGE, PARITY, AND ANTENATAL CARE VISITS AS PREDICTORS OF CESAREAN SECTION DELIVERY AT TK II MARTHEN INDEY HOSPITAL, JAYAPURA - Rahmadani, Ulfa; Vrensca C M Rupilu; Fika Daulian; Syaharuddin Nur; Faridha Almira; Wilma Florensia; Anneke Yacob; Ristina Rosauli Harianja (International Journal of Social Science, 2024)
Background: Cesarean section (CS) rates have been increasing in Indonesia, including in Papua, raising concerns about maternal and neonatal outcomes. Antenatal care (ANC) is a key intervention to monitor pregnancy and prevent complications. Objective: This study aimed to determine the association between maternal age, parity, and ANC Visits with cesarean section delivery at TK II Marthen Indey Hospital, Jayapura. Methods: An analytical observational study with a cross-sectional design was conducted in 2017. The study population consisted of all delivering mothers, with a sample of 149 respondents selected based on specific inclusion and exclusion criteria. Data were obtained from medical records, including variables on maternal age, parity, ANC visits, and medical history. Univariable, bivariate (Chi-square), and multivariable (logistic regression) analyses were performed to identify dominant factors associated with CS. Results: Of 149 respondents, 57.0% delivered by CS, exceeding the WHO recommended rate (5–15%). Multivariable analysis showed that maternal age <20 or >35 years (aOR=1.6; 95% CI: 1.02–2.85; p=0.042), primiparity (aOR=1.9; 95% CI: 1.08–3.60; p=0.038), and irregular ANC visits (aOR=3.8; 95% CI: 2.00–7.20; p=0.001) were significantly associated with CS. The model showed good fit (Hosmer–Lemeshow p=0.47, Nagelkerke R²=0.32) and discrimination ability (AUC=0.76). Conclusion: Maternal age, primiparity, and ANC Visits are significant predictors of cesarean section delivery, with irregular ANC being the dominant factor. Interventions promoting regular ANC visits, particularly for high-risk mothers, are recommended to reduce unnecessary CS.